Perancangan Sensor Water Level Menggunakan Nirkabel - Rizqi Satrio, Nur; Romadhon Parada Dian Palevi, Bima; Ardita, Michael (Jurnal FORTECH, 2025)
The design of the wireless water level sensor system aims to monitor water in the river effectively and efficiently. The system utilizes wireless technology to transmit data in real-time, allowing users to monitor water levels remotely. In this project, the water level sensor was selected for its high accuracy in measuring the depth of the water. The data collected by the sensors will be transmitted via a wireless communication module such as LoRa that we use to a web-based application or mobile device, where the user can visually monitor the status of the water level. The system test method is carried out by monitoring the results of water level identification in the river to ensure accuracy. The results show that the system not only provides accurate data, but also reduces the need for manual intervention, thereby improving operational efficiency. In addition, the implementation of this system also provides convenience in disseminating information warning of the existence of. With the application of wireless technology, these sensor systems have the potential to be applied in various sectors, including agriculture, industry, and water resource management. This research is expected to be the foundation for further development in intelligent and sustainable environmental monitoring.